Genome-wide identification of growth−regulating factor and GRF−interacting factor gene families across three Solanaceae species with functional analysis in pepper regeneration - Wang, Yanping; Jia, Li; Wang, Han; Zhou, Xiujuan; Yan, Congsheng; Ding, Qiangqiang; Hong, Xiujing; Dong, Yanxiang; Wang, Yan; Jiang, Haikun (Frontiers in Plant Science, 2025)
The growth-regulating factor (GRF) and GRF-interacting factor (GIF) gene families play crucial roles in enhancing plant genetic transformation efficiency. However, the functional contributions of pepper GRF and GIF genes in improving transformation efficiency remain unexplored. In this study, we identified 31 GRF genes and 9 GIF genes across pepper, tomato, and tobacco. A systematic analysis was conducted to characterize their phylogenetic relationships, gene structures, collinearity, and expression patterns. Collinearity analysis revealed large-scale duplication events among these three Solanaceae species. Furthermore, qRT-PCR analysis demonstrated significantly elevated ex-pression levels of pepper GRF and GIF genes in regenerative tissues, indicating their critical functional roles during pepper regeneration processes. Our findings provide novel insights into the evolution of GRF and GIF gene families in Solanaceous plants and identify several key candidate genes for future functional studies aimed at enhancing pepper regeneration efficiency and genetic transformation.